Professional practices and employability skills training - Marta Ruiz-Corbella; Maria José Bautista-Cerro Ruiz; Miriam García-Blanco (Universidad de La Rioja, 2019)
In the design of university degrees one of the fundamental points that guarantees their viability is the employability of its graduates. Guaranteeing insertion in the labor market is one of the key objectives promoted by different organizations, which means that, from different university instances, initiatives aimed at their achievement are promoted. Now, this employability will not be attained without learning the specific and generic skills from each Bachelor degree in order to design ones professional project as well as the means to face the transition into the working life with a guarantee of success. With this aim, the subject Professional Practices V of the Degree in Social Education of the UNED develops an experience of teaching innovation directed to know how to elaborate an own Professional Project. The search and collection of information, its analysis, as well as taking well-founded decisions and proposing a professional strategy, provide the key elements to manage their employability for the incorporation into the labor market. The results of this experience are collected with a longitudinal methodology "ex post-facto" through the score received in this subject and the results of the questionnaires of student satisfaction. The experience throughout 5 academic years supports the training of our students in competencies for employment, as well as their high level of satisfaction with such training.